Oxydromus Grube, 1855 reinstated over Ophiodromus Sars, 1862 (Polychaeta, Hesionidae) - Villalobos-guerrero, T.; Harris, L. (ZooKeys, 2012)
The hesionid polychaete genera Oxydromus Grube, 1855 and Ophiodromus Sars, 1862 have been regarded as synonyms with the former considered as invalid since it was thought to be a junior homonym of Oxydromus Schlegel, 1854. However, Schlegel's name is an incorrect subsequent spelling for Ocydromus Wagler, 1830 (Aves, Gruiformes, Rallidae) and is not an available name. Consequently, Oxydromus Grube, 1855 must be reinstated for this hesionid polychaete genus. A check-list of valid species of Oxydromus including 30 new combinations is provided.
World Polychaeta Database (WPolyD)